2017
DOI: 10.5539/ijms.v9n2p146
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Consumer Impulse Buying Behaviour from a Range of Consumer and Product Related Factors

Abstract: The main purpose of this study is to explore the consumer impulse buying behaviour from a range of consumer and product related factors. To achieve this purpose, the study was guided by five research questions in the area of product physical quality, product price, product attractiveness, product origin, and purchase location. The study employed quantitative method. A sample of 179 respondents (consumers) that visited the Accra Shopping Mall was employed using convenient selection method. A self-completed 5 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…It is a solid urge to possess the desired thing with little restriction to refuse. Impulse purchasing is a strong desire to make an instant, unexpected purchase (Yeboah and Owusu-Prempeh, 2017). Similarly, moderation results revealed that SET (H6) and MT (H7) had a robust moderating effect between IBT and CB, and these results were supported by Atulkar and Kesari (2018) and Lavuri et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a solid urge to possess the desired thing with little restriction to refuse. Impulse purchasing is a strong desire to make an instant, unexpected purchase (Yeboah and Owusu-Prempeh, 2017). Similarly, moderation results revealed that SET (H6) and MT (H7) had a robust moderating effect between IBT and CB, and these results were supported by Atulkar and Kesari (2018) and Lavuri et al.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have revealed that the stimuli elements influence impulsive buying behavior by inducing impulse purchasing inclinations in consumers. Extrinsic factors, such as SE, product characteristics, PA and stimulating factors are explored (Yeboah and Owusu-Prempeh, 2017), which affect shoppers’ IBT. Such a high IBT would be stronger and more likely to have impulsiveness (Darrat et al ., 2023; Lavuri et al ., 2023b; Barakat, 2019).…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…Because by shopping for the things you want, your mood will be happier, happier, and other positive moods. Good product quality has an impact on consumer satisfaction or pleasure so that it will trigger unplanned purchases [10]. Thus, the incentive to make unplanned purchases will be high if the products produced are also of good quality.…”
Section: Muslim Clothing Groupmentioning
confidence: 99%
“…▪ Dimensão localização: A localização das lojas de varejo, sejam elas pequenas, de departamentos ou grandes supermercados, torna o ponto uma influência na escolha dos consumidores, pois considera-se o custo de transporte, bem como a localização ambiental ao tomar a decisão pela compra (YEBOAH;PREMPEH, 2017).…”
Section: Marketing De Serviços Em Supermercadosunclassified